The G-20 Presidency as an External Political Instrument to Realize Good Environmental Governance in Indonesia - Olifiani, Laras Putri; Elyta, Elyta (International Journal of Education, Vocational and Social Science, 2023)
This article will discuss Indonesia's plan to relocate the capital city which is faced with problems and skepticism related to potential environmental damage, while Indonesia has the opportunity to hold the Presidency of the G-20, which is one of the leading institutions for global environmental issues. Since 1970 until now, environmental issues have attracted much attention and have become one of the main agendas implemented by countries and international organizations, one of which is the G-20, a multilateral forum for global economic and financial cooperation. Several years ago, the G-20 added environmental issues as the main agenda of the collaboration. Along with this, in 2022, Indonesia was elected to the G-20 Presidency. Leadership in the G-20 forum has strategic meaning and benefits for Indonesia. This research will use explanatory methods and literature study data collection techniques as legitimacy for the scientific validity of this paper. Through the theory of global environmental governance and the concept of good environmental governance, this research seeks to find relevance between the existence of the G-20 and Indonesia's efforts to relocate capital cities that have the potential for ecological damage. The study results show that the G-20 can positively contribute to the realization of moving the Indonesian capital city with indications of prevention and mitigation of environmental damage. This research seeks to find the relevance between the existence of the G-20 and Indonesia's efforts to relocate the capital city, which has the potential for environmental damage.